The Effectiveness of Teaching Reading by Using Jumbled Pics Stories - Lenny Eka Saputri; Muhamad Sofian Hadi (Universitas Pendidikan Mandalika, 2021)
The aim of the research was to find out if there was any significant improvement on student’s reading after being taught through Jumbled Pics Stories at 9th grade of students at SMP Al-Fitroh Tangerang. The method used in this research was the quantitative method of pre-experimental design by implementing pre-test and post-test design. In this study, the researcher used 15 students as a sample. The data were corrected by pre-test and post-test as instruments. The result of the study was calculated using t-test. The findings showed that student’s post-test scores mean (64.33) were higher than pre-test scores mean (71.86). By using t-test, the result of t-table with degrees of freedom (df) 14 reached 7.92. The finding revealed that Jumbled Pics Stories is effective media to improve student’s reading.